2001
DOI: 10.1002/qre.391
|View full text |Cite
|
Sign up to set email alerts
|

On misinterpretation of the asymptotic property of system time‐between‐failures

Abstract: SUMMARYIf a system, not necessarily one in series, is composed of components having various time-to-failure distributions and components are replaced good-as-new as they fail, then the system time-between-failure distribution tends toward the exponential. Many practicing reliability engineers, incorrectly invoking this property, model their systems with an exponential time-to-failure. We show, under two conditions, using a hypothetical fleet of vehicles, the severity of this error. Modeling time-to-failure as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…The guidelines to determine uncertainty of several failures in configured testing may have been offset by the time conversion technique.Hypothesis testing proved the existence of hardwaresoftware-human failures and affirmed a multi-element integrated model to quantify failures. The analysis also confirmed that traditional assumptions of MTBF (Ref 4). are not permitted in unique environments without thorough investigation into the nature of data.…”
supporting
confidence: 64%
“…The guidelines to determine uncertainty of several failures in configured testing may have been offset by the time conversion technique.Hypothesis testing proved the existence of hardwaresoftware-human failures and affirmed a multi-element integrated model to quantify failures. The analysis also confirmed that traditional assumptions of MTBF (Ref 4). are not permitted in unique environments without thorough investigation into the nature of data.…”
supporting
confidence: 64%
“…In many cases, this assumption is misinterpreted by practicing engineers in modeling their system. This misinterpretation can cause excessive sparing and resource allocation based on inappropriate analysis using a component or subsystem exponential failure distribution [3]. Furthermore, the time-to-failure (TTF) distribution, or the time-to-first-failure (TTFF) distribution typically is significantly different from the exponential.…”
Section: Introductionmentioning
confidence: 99%